1996
DOI: 10.1007/s004410050745
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional organization of the developing vasculature of the kidney

Abstract: Abstract. Kidney function depends on a well-developed vascular system. Any impairment of the blood supply disturbs the integrity and function of the organ. The differentiation of renal vessels has been investigation for many years, but little is known about the relationship between nephrogenesis and vessel development. In the present work the spatial organization of the differentiating vessels was analyzed in precisely oriented tissue sections and in optical sections acquired by laser scan microscopy. Developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…This was surprising as previous work had suggested that these peripheral vessels are of a vasculogenic origin, are predominantly non-perfused 17 , and do not have a lumen at this stage (in rabbit ref. 36). Therefore, we expected an absence of erythroid cells.…”
Section: Resultsmentioning
confidence: 99%
“…This was surprising as previous work had suggested that these peripheral vessels are of a vasculogenic origin, are predominantly non-perfused 17 , and do not have a lumen at this stage (in rabbit ref. 36). Therefore, we expected an absence of erythroid cells.…”
Section: Resultsmentioning
confidence: 99%
“…Some cells inside the CD ampullae represent renal stems cells growing in a tissue layer that lacks functional blood vessels. 23 In perfusion culture the cells of the CD ampulla have been shown to develop into a functional epithelium showing features of adult principal and intercalated cells. 17 It has been shown earlier that the development of embryonic collecting duct cells can be influenced by the application of aldosterone [24][25][26] as well as by urea 27 and increased electrolyte concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The typical three-dimensional structure of the developing renal vascular network (Fig. 1a) [30] could only be preserved in the presence of the growth and differentiation factors (Table 1 and Fig. 2).…”
Section: Culture Strategymentioning
confidence: 98%